Cyst-theca relationships of Gonyaulacales and Peridiniales (Dinophyceae) from Bahía Concepción, Gulf of California - Morquecho, Lourdes; Góngora-González, Diana T.; Okolodkov, Yuri B. (Instituto de Ecología, A.C., 2009)
Based on samples obtained in 2000-2002 from a 1-cm layer of surface sediment at two sites in Bahía Concepción in the Gulf of California, cyst-theca relationships were defined from cyst germination assays for Gonyaulax spinifera (= Spiniferites mirabilis), Protoce- ratium globosum, Preperidinium meunieri (= Dubridinium caperatum), Protoperidinium denticulatum (= Brigantedinium irregulare), and Protoperidinium cf. thorianum. All the taxa are illustrated with photomicrographs and descriptions of the resting and vegetative stages are given, including synonymy, size variation, distribution in Mexico, and global distribution, when known. As a result of cyst germination assays, the previously unknown cyst-theca relationship of P. globosum was described. We also confirmed the presence of the vegetative stage of P. denticulatum in the Gulf of California and heterospory in G. spinifera from Bahía Concepción. Cultures of G. spinifera and P. globosum were successfully established.